Soil Organic Carbon Increases With Decreasing Microbial Carbon Use Efficiency During Vegetation Restoration - Jingwei Shi; Lei Deng; Jianzhao Wu; Edith Bai; Ji Chen; Zhouping Shangguan; Yakov Kuzyakov (Global Change Biology, 2024)
Microbial carbon (C) use efficiency (CUE) describes the proportion of organic C used by microorganisms for anabolic processes, which increases with soil organic C (SOC) content on a global scale. However, it is unclear whether a similar relationship exists during natural vegetation restoration in terrestrial ecosystems. Here, we investigated the patterns of CUE along a 160‐year vegetation restoration chronosequence (from farmland to climax forest) estimated by stoichiometric modeling; additionally, we examined the relationship between CUE and SOC content and combined these results with a meta‐analysis. The combination indicated that vegetation restoration decreased CUE from 0.35 to 0.28. Surprisingly, SOC content increased with decreasing CUE during vegetation restoration because forest soils have low pH values and high microbial phosphorus limitations compared to early ecosystems, implying that climax forests may not sequester as much soil C as expected. The shift in soil pH was the most important predictor of CUE compared to climate, plant, and microbial factors. CUE changes were directly induced by soil pH and not by the pH‐induced microbial community. Alkaline soil acidification tended to decrease CUE. This first large‐scale estimate of the relationship between CUE and SOC during natural restoration highlights the need to strengthen C sink management in mature forests to sustain their C sequestration potential.